Endogenous lysophosphatidic acid (LPA1) receptor agonists demonstrate ligand bias between calcium and ERK signalling pathways in human lung fibroblasts - Sattikar, Afrah; Dowling, Mark R,; Rosethorne, Elizabeth M. (Wiley, 2017)
Background and Purpose